Analysis of the Supermarket Environment for Elderly: a Case Study (Human Factors in Design, 2017)
The article aims to analyze the experience of the elderly in a supermarket, in order to identify the difficulties and tools of assistive technologies available to assist them in the task. Through a theoretical reference on the elderly, the supermarkets environment and accessibility, a case study was carried out in which three elderly women were observed while they were shopping. The results showed that the environment does not have assistive technologies, nor does it help the elderly in their purchases, in addition to some sectors that are not accessible. This research is expected to consolidate knowledge about the subject, a special attention for this growing public that needs more care.